عقد التسيير المفوض The Authorized Management Contract - ياسين, مقدم (Université de M'sila, 2020)
يقصد بتفويض المرفق العمومي لأحد أشخاص القانون العام أو الخاص ، التفويض للتسيير فقط دون الاستغلال و عدم التنازل الكلي عن المرفق العام و ذالك في الإطار التعاقدي. وقد لجأت الجزائر إلى هذا النمط من التسيير بعد الانفتاح الاقتصادي و ذلك من خلال احتفاظ الدولة و الجماعات المحلية بملكية وتنظيم المرافق العامة مع التخلي عن تسييرها لشخص أخر. إن المشرع الجزائري بتدخله لتنظيم عقد التسيير المفوض بموجب الأمر الرئاسي 15/247 يكون قد خطا خطوة كبيرة في تنظيم تقنية جد مهمة لما لها من دور كبير في تحسين أداء المرافق العمومية و القضاء على ظاهرة البيروقراطية التي ما فتئت تنغص على المواطن حياته، و تفرمل كل مظاهر التطور و تكبح مجهودات التنمية الوطنية، كما انه جاء في فترة جد ملائمة تتميز بالصعوبات المالية التي يعرفها الاقتصاد الوطني، وكذا انتشار ظاهرة الفساد التي أصبحت تلازم الكثير من الصفقات العمومية، كما أن تطوير عقد التسيير المفوض يمكن المقاولين من اكتساب خبرات و تجارب تمهد لتطوير ميدان المقاولاتية في الجزائر. By the delegation of a public facility to a person of public or private law,it is often meant the authorization to conduct only without exploitation and the total renunciation of the general facility and the contractual framework. Algeria has resorted to this mode of governance after economic openness through the retention of the state and local groups ownership and the organization of public utilities while giving up its management to another person. The Algerian legislator ,intervening to organize the management contract mandated by presidential order 15/247 ,has taken a step in organizing a very important technology because of its role in improving the performance of public utilities and eliminate the phenomenon of bureaucracy.In fact , the development of the authorized management contract enables contractors to acquire experiences that will pave the way to the development of the national economy, as well as the spread of the phenomenon of corruption that has become associated with many public transactions. The field of contractors in Algeria.
Keywords: المرفق العمومي، تفويض التسيير ، عقد التسيير المفوض، الصفقات العمومية ; The public facility , the authorization to conduct, the authorrized management contract , public transactions.